Spraying of oxytetracycline and gentamicin onto field-grown coriander did not affect the abundance of resistant bacteria, resistance genes, and broad host range plasmids detected in tropical soil bacteria - Rodríguez Sánchez, César (2008)
Horticultural supplements containing oxytetracycline and gentamicin, two clinically relevant biocides, are widely marketed to prevent or control infections by bacterial phytopathogens. Despite their regular consumption in the world’s less developed countries, it is unknown whether exposure of tropical farmlands to these drugs results in an enrichment of resistant bacteria, resistance genes, and/or mobile genetic elements in the soil. These concerns were investigated under field conditions by repeatedly spraying recommended amounts of a commercial product containing oxytetracycline-HCl, and gentamicin- SO4-2 onto two coriander plots. Subsequent to five applications within 16 months, composite soil samples from control and treated sections were compared with respect to the abundance of resistant bacteria and the prevalence of conserved nucleotide sequences from tetracycline efflux proteins, tetracycline ribosomal protection proteins, four different families of gentamicin-modifying enzymes, and broad host range plasmids of the IncP-1 and IncQ incompatibility groups. The isolation frequency of oxytetracycline- and gentamicin-resistant bacteria and the detection rate of the aforementioned genes and elements were unrelated to application of the supplement. Despite the omnipresence of sequences from IncP-1 plasmids, conjugative plasmids conferring resistance to oxytetracycline or gentamicin were not captured in biparental matings. The widespread occurrence of resistant bacteria and resistance genes at the beginning of the trial emerges as a reasonable explanation for the lack of anticipated responses. Moreover, we assume that the biocides applied were inactivated by biotic and abiotic factors under tropical conditions.